Sources, Compositions, and Health Risks of PM2.5-bound PAHs at the Rural Area along with the “Coal to Gas” Law - Zhiyong Li; Ziyuan Yue; Wenjia Zhu; Wenquan Liu; Jintao Gao; Jiaqiang Zhang; Ziyi Zhan; Lan Chen; Huiying Gao; Jihong Wei (Aerosol and Air Quality Research)
Abstract The “Coal to Gas” (CTG) policy in north China markedly altered the characteristics of polycyclic aromatic hydrocarbons (PAHs) in PM2.5. Existing researches about CTG impacts on components, sources, and health risks of PM2.5-bound PAHs mainly focused on metropolitan area, whereas they were lacking in rural area of north China. Here, we deployed an intensive observation in winter of 2020 at a rural site in the central area of the Beijing-Tianjin-Hebei (BTH) region. A positive matrix factorization (PMF) model and an incremental lifetime cancer risk (ILCR) model were utilized to examine the PAH sources and health risks. Higher daily average PM2.5 of 81.5 µg m−3 in the sampling period than 75 µg m−3 of the National Air Quality Standard Grade II indicated the air pollution in rural area was still serious. The total PAHs increased obviously from diurnal 86.2 ng m−3 to nocturnal 151 ng m−3 because of the nocturnal high intensity of heating, with the increases of 20.7%, 85.5%, and 76.3% for low, medium, and high molecular weight PAHs, respectively. Vehicular exhaust (VE), coal burning (CB), industrial source (IS), biomass burning (BB), and oil spill and leakages (OSL) were the main PAH contributors, with the average daily contributions of 32.7%, 21.5%, 18.3%, 15.9%, and 11.6%, respectively. Lower CC contribution of 27.6% in winter of 2020 than 27.6% in winter of 2019 indicated the positive role of CTG policy. However, the nocturnal CC fraction increased by 680% compared with the diurnal value, and CC had become the largest contributor in the nighttime. BB contribution was up to 18.3%, evidencing that biomass utility should be managed in term of the biomass burning was prohibited in BTH rural area. Moreover, the nocturnal average BaPeq equivalent concentration exhibited higher levels than those in the daytime. The nocturnal ILCR values of adults and children was 9.35 × 10−6 and 2.66 × 10−6, exceeding the acceptable threshold, suggesting there was a potential carcinogenic risk.